Case Report: IVIG causing bilateral papilledema and increased intracranial hypertension in patients with anti-TIF-1γ antibody-positive JDM - Baluta, Sarah; Stojkic, Ivana; Driest, Kyla; Schutt, Christina (Frontiers in Pediatrics, 2024)
Juvenile dermatomyositis is a systemic autoimmune disease characterized by progressive proximal muscle weakness, pathognomonic rashes, and often myositis specific antibodies. Consensus treatment plans for pediatric patients with juvenile dermatomyositis recommend steroids and methotrexate as initial therapy. Patients with anti-TIF-gamma antibodies tend to have more refractory disease requiring more aggressive treatment with intravenous immunoglobulin that is typically well tolerated. We describe two pediatric patients diagnosed with anti-TIF-1-gamma antibody positive juvenile dermatomyositis who developed persistent increased intracranial pressure with intravenous immunoglobulin treatment. These cases suggest a potential association between treatment with intravenous immunoglobulin and increased intracranial pressure that is not a readily known side effect. The shared anti-TIF-1-gamma positivity in both patients may suggest a possible concern for intracranial hypertension among juvenile dermatomyositis patients with this myositis specific antibody.